Berita Anjuran Poligami Bagi Kader Partai Keadilan Sejahtera di Media Online: Framing Zongdang Pan dan Gerald M. Kosicki - Ahmad Adnan; Sunaryanto Sunaryanto; Ahmad Rofi Syamsuri (Institut Agama Islam Tribakti (IAIT) Kediri, 2022)
This study interprets the discourse on polygamy recommendations for cadres of the Prosperous Justice Party (PKS) which is framed in national online news media. The national media selected as research objects are Kompas, Sindonews, and CNN Indonesia. News as the unit of analysis is the recommendation of polygamy for PKS cadres in the three online media. News is limited to 1 (one) news each, namely specifically published on September 30, 2021. The theory used to answer the discourse is the framing of Zongdang Pan and Gerald M. Kosicki. The conclusion of the study is that Kompas, Sindonews, and CNN Indonesia developed framing to disagree with the idea of polygamy for PKS cadres. The three online media construct the reality of polygamy recommended news for PKS cadres by developing framing with their respective goals. There is an ideological interest in the news construction built by the three online media